2011
DOI: 10.3109/09638288.2011.642927
|View full text |Cite
|
Sign up to set email alerts
|

Attendance at a psychological support group for people with multiple sclerosis and low mood

Abstract: Men were less likely to attend group treatment sessions than women, but no other variables were associated with non-attendance. Attendance rates influence the effectiveness of interventions and reasons for non-attendance need to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The therapeutic effects of the attending support groups has been documented in various conditions, such as cancer (Goodwin et al, 2001), and MS (Holmes, Ford, Yuill, Drummond, & Lincoln, 2012;Lincoln et al, 2011); and was endorsed by all three groups in our study. Research in ageing has indicated that psychological and social factors, including lifestyle-related activities have an interaction effect that may reduce adverse effects of brain dysfunction on cognition (e.g., Dawson, Winocur, & Moscovitch, 1999).…”
Section: Therapeutic Effects Of the Groupsupporting
confidence: 63%
“…The therapeutic effects of the attending support groups has been documented in various conditions, such as cancer (Goodwin et al, 2001), and MS (Holmes, Ford, Yuill, Drummond, & Lincoln, 2012;Lincoln et al, 2011); and was endorsed by all three groups in our study. Research in ageing has indicated that psychological and social factors, including lifestyle-related activities have an interaction effect that may reduce adverse effects of brain dysfunction on cognition (e.g., Dawson, Winocur, & Moscovitch, 1999).…”
Section: Therapeutic Effects Of the Groupsupporting
confidence: 63%
“…MS may cause cognitive disturbance or dementia and, less often, organic psychopathology encompassing behavioural/personality disturbance, mood/affective disorders or psychosis. 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104 Psychiatric syndromes, such as bipolar disorders and atypical psychosis, often unassociated with cognitive disturbance or dementia, have been described, and euphoria sclerotica is a characteristic psychosyndrome in MS. 83, 84, 85, 89, 91, 94, 95, 96, 99, 104, 105, 106, 107 Pure psychiatric presentation in MS is rare, as is the case for CTX. 83, 89, 91, 106, 107 Major depressive disorder, which often is prodromal leading to diagnostic delay, is overrepresented in MS patients, as are suicidal ideation, anxiety and sleep disorders, and they are mainly believed to be secondary to physical illness and/or disease-modifying treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While all participants had low mood and multiple sclerosis, this in itself may not have been sufficient to foster cohesion. For the Holmes et al 16 study, non-attendance was more common among men than women. They were in the minority in each group and may not have been able to connect to the others.…”
Section: Discussionmentioning
confidence: 99%
“…Attendance at group sessions has been found to be a problem previously and the proportion attending was consistent with that found in previous research. 16 One hypothesis is that the success of the groups is dependent on group cohesion, which is often linked to shared identities, ideologies, and interests. While all participants had low mood and multiple sclerosis, this in itself may not have been sufficient to foster cohesion.…”
Section: Discussionmentioning
confidence: 99%